Design of Rectangular Microstrip Patch Antenna for 2.4 Ghz Applied a Wban - Kaschel-Carcamo, H (Institute of Electrical and Electronics Engineers Inc., 2018)
This paper presents a design of rectangular microstrip antenna patch applied a WBAN (Wireless Body Area Network). The antenna is designed over the operating frequency is 2.4 GHz using the substrate material as FR-4 which has the dielectric constant of 4.3. The designed antenna can be used for ISM (industrial, scientific and medical) band and UWB applications. The designed antenna has low profile, low cost, easy fabrication and good isolation. The antenna is designed by using CST simulation software and designed antenna provides return loss less then-10 dB. The proposed antenna is designed with the purpose of obtaining a low SAR models of the human body, considering both the electromagnetic effect and the shell model in human tissues. © 2018 IEEE.
Keywords: Electromagnetic compatibility (EMC); Microstrip Antenna; Specific Absorption Rate (SAR); Wireless Body Area Network (WBAN)